COMPARATIVE TAXONOMICAL STUDY FOR REPRODUCTIVE PART OF EIGHT SPECIES BELONG TO BRASSICACEAE FAMILY IN IRAQ - Sukeyna A. A.,; Lobab G.A.,; Hadeel R. H. Al-Newani, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed description of morphological features of fruits and seeds of eight species related to Brassicaceae family in Iraq, the study showed number of taxonomic differences as the silique was long in all studied except the species Rorippa amphibian (L.)b Besser was short, however the  fruits varied in dimensions where the species Turritis laxa L. recorded the highest average length with (160 mm) while the species  R .amphibia was record  the shortest length (5 mm), in addition the colors ranged from green to brown. This study showed that all of the species was glabrous except Arabis caucasia Willd. was lanute-woolly.  The configuration shapes were linear with except the species Nasturtium officinale W.T.Aiton. was elliptic and R.amphibia was ovoid, moreover, the characteristics of   seeds were investigated as taxonomical important traits like dimensions, colors, number of seeds in fruit, surface configuration and the presence of wing, the number of seeds per species as T. laxa have about 75 seeds  in one fruit with the highest rate recorded while lowest average number of seeds among species was 12 seeds in Arabis novaVill.